The impact of the use of information technology on the utilization of knowledge management in the Ministry of Environment, Water and Agriculture in the Kingdom of Saudi Arabia (The International Journal for Scientific Research, 2022)
The current study aimed to know the reality of the impact of the use of information technology on the extent to which knowledge management is used in the Ministry of Environment, Water and Agriculture. Given the breadth of the concept of information technology, the main focus of the study is on management information systems. As for the areas of benefiting from knowledge management, they include improving: the planning process, the efficiency of workers' performance, project management activities, the decision-making process, the quality of services, innovation and creativity, and performance excellence.The study used the descriptive approach and the case study approach to describe the reality of the management information systems used in the ministry and the reality of their support for areas of benefit from knowledge management. The questionnaire and the personal interview were used as data collection tools. The total population of the study includes managers at the level of senior management and middle management, and workers in the general administration of information technology. The questionnaire was applied to a sample of 140 participants.The study concluded that the respondents on the whole agree to some extent on the "elements of management information systems", "areas of benefiting from knowledge management", but they do not agree with software resources, improving the efficiency of workers' performance, improving the quality of services provided to citizens, and improving the organization's ability to innovate and create, and neutral in terms of human resources, and improve the quality of the decision-making process.The study recommended the necessity of having a department in the organizational structure specialized in knowledge management, and the need to pay attention to the employment of specialists in the field of knowledge, and it recommended the need to improve human resources and software resources. It also recommended increasing attention to improving the quality of the decision-making process, improving the efficiency of workers' performance, improving the quality of services provided to citizens, and improving the organization's ability of innovation and creativity.
Keywords: Information Technology; Management Information Systems; Utilization Areas of Knowledge Management; Knowledge Management Applications; Government Organizations